Can sheep help to improve positive emotions, mindfulness, and self-efficacy expectancy? A pilot study of animal-assisted intervention as an enhanced CBT-based therapy for substance use disorders - Schmid, Petra; Nauss, Carmen; Jauch-Ederer, Claudia; Prinz, Petra; Tschöke, Stefan; Uhlmann, Carmen (Frontiers in Psychiatry, 2024)
Introduction Substance use disorders (SUDs) are common, and there is evidence of clinically significant benefit of cognitive behavioral therapy (CBT). The efficacy of CBT in SUDs has been confirmed, although relapse rates of 40%–60% have been reported. An enhancement of CBT-based therapy through an animal-assisted intervention (AAI) with sheep to normalize the occurrence of negative emotions and improve positive emotions as well as mindfulness and self-efficacy expectancy was investigated. Methods A single-session AAI with sheep in a group setting was investigated against treatment as usual over time. N = 36 psychiatric inpatients with SUDs were examined by questionnaires before and 1 week after the intervention and additionally immediately after the intervention. Results Positive emotions improved significantly in the AAI group 1 week after the intervention with a medium effect size, but not in the control group. Similarly, mindfulness and self-efficacy expectancy improved over time in the AAI group. When exploratory results were evaluated immediately after the intervention while still on the farm, the effects in favor of AAI were even larger. Conclusions AAI can thus be considered effective in improving positive emotions, mindfulness, and self-efficacy expectancy. The impressive effect sizes immediately after the intervention encourage us to consider what can be done to maintain these even greater effect sizes over time. Clinical Trial Registration https://drks.de/search/de/trial/DRKS00027539, identifier DRKS 00027539.